Pandemic and partisan polarisation: voter evaluation of UK government handling during Covid-19 - Vlandas, T; Klymak, M (Wiley, 2021)
What is the effect of pandemics on partisan perceptions of government competence? Taking the case of Covid-19 in the UK, we explore how voters’ assessments of the government’s handling of the economy and health were affected by four events: the first UK Covid-19 death; the national lockdown; Boris Johnson’s hospitalisation; and Cummings’ scandal. Using a large representative weekly survey in the last year totalling over around 30’000 respondents, our results show that Labour voters had the worst assessments of government handling. The first death deteriorated perceptions of government handling of health among both Labour and Conservative voters, while Boris Johnson’s hospitalisation improved perceptions among most voters. Lockdown improved the perception of health handling but at the cost of more negative perceptions of its handling of the economy. The Cummings scandal had a negative effect on perceptions of government handling of economy but surprisingly improved perceptions of its handling of health.